Prior treatment with oxaliplatin-containing regimens and higher total bilirubin levels are risk factors for neutropenia and febrile neutropenia in patients with gastric or esophagogastric junction cancer receiving weekly paclitaxel and ramucirumab therapy: a single center retrospective study - Katsuhiko Nara; Takehito Yamamoto; Hiroharu Yamashita; Koichi Yagi; Tappei Takada; Yasuyuki Seto; Hiroshi Suzuki (BMC Cancer, 2023)
Abstract Background Weekly paclitaxel + ramucirumab (wPTX + RAM) therapy is recommended as the standard second-line chemotherapy regimen for unresectable advanced/recurrent gastric cancer (GC) or esophagogastric junction cancer. Recent subgroup analysis of the RAINBOW trial revealed a higher frequency of severe neutropenia due to wPTX + RAM in Japanese compared to Western patients. However, no risk factors for severe neutropenia have been identified. Methods This retrospective observational study included patients with advanced/unresectable gastric or esophagogastric junction cancer who received wPTX + RAM after failure to respond to platinum and fluoropyrimidine doublet chemotherapy between June 2015 and April 2020. We conducted multivariable logistic regression analyses to identify the risk factors associated with grade 4 neutropenia and febrile neutropenia (FN). In addition, we investigated the relationship between the number of risk factors and overall survival (OS) and progression-free survival (PFS). Results Among 66 patients who met the inclusion criteria, grade 4 neutropenia and FN occurred in 21 (31.8%) and 12 (18.2%) patients, respectively. Prior treatment with oxaliplatin-containing regimens was identified as an independent risk factor for developing grade 4 neutropenia (odds ratio (OR) 20.034, 95% confidence interval (95% CI) 3.216–124.807, P = 0.001). Total bilirubin of > 1.5 mg/dL (OR 31.316, 95% CI 2.052–477.843, P = 0.013) and prior treatment with oxaliplatin-containing regimen (OR 12.502, 95% CI 1.141–137.022, P = 0.039) were identified as independent risk factors for developing FN. Next, we classified patients with 0, 1, 2 risk factor(s) as RF-0, RF-1, and RF-2 subgroups, respectively, and compared the PFS and OS among the three subgroups. PFS was not significantly different among the three subgroups, whereas OS was significantly shorter in the RF-2 subgroup (median 1.4 month, 95% CI 0.0–5.3 month) than in the RF-0 subgroup (median 10.2 month, 95% CI 6.8–13.5 month, P < 0.01 vs RF-2) and RF-1 subgroup (median 13.3 month, 95% CI 10.9–15.7 month, P < 0.01 vs RF-2). Conclusions Careful monitoring for grade 4 neutropenia and FN is needed for patients receiving wPTX + RAM therapy who have a history of treatment with oxaliplatin-containing regimens and higher total bilirubin levels.